2001
DOI: 10.1136/pmj.77.908.392
|View full text |Cite
|
Sign up to set email alerts
|

Survey of hospital doctors' attitudes and knowledge of oral conditions in older patients

Abstract: The study was designed to assess the views and knowledge of hospital doctors in general and geriatric medicine on oral health in older people. Eighty two doctors in general and geriatric medicine at two hospitals were shown 12 colour slides of oral mucosal conditions and asked to give a diagnosis for each slide and complete a questionnaire. Completed questionnaires with the answers to the coloured slides were returned completed by 70 doctors.The majority of doctors (84%) felt it was important to examine older … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 9 publications
4
20
0
2
Order By: Relevance
“…sicians, as evidenced by other studies (13)(14)(15). On the other hand, patients felt that they would be more careful about oral hygiene if they were informed.…”
Section: Research Design Andmentioning
confidence: 62%
“…sicians, as evidenced by other studies (13)(14)(15). On the other hand, patients felt that they would be more careful about oral hygiene if they were informed.…”
Section: Research Design Andmentioning
confidence: 62%
“…[7] Previous study among non-dental resident doctors in Nigeria on the knowledge of dental specialty revealed that only 5.6% had good knowledge. [8] Morgan et al .,[9] reported that insufficient training and lack of confidence were among the reported reasons for failure of a significant proportion of physician to conduct oral examination which is part of the physical examination.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study 30% of doctors said they would prescribe nystatin for oral candidiasis on the request of nursing staff without examination of the oral cavity. 16 This is unfortunate as other pathology may be missed, the diagnosis may be incorrect, and failure to address risk factors may lead to recurrence of the candidiasis.…”
mentioning
confidence: 99%